TRAFFIC DENSITY DUE TO MOTORCYCLE NOISE DURING THE PANDEMIC COVID-19 - Syaiful, Syaiful; Siregar, Hermanto; Rustiadi, Ernan; Hariyadi, Eri Susanto; Ardila, Fitri Aning Dwi; Akbar, Chaeka Fitria Ramadhania (ASTONJADRO, 2021)
The density of motorized vehicles, especially motorcycles on the highway, is getting higher. However, in line with the 2020 Covid-19 pandemic, it has an impact on the decrease in the number of motorized vehicles on the highway. The density of motorcycles has a significant effect on noise, from all analysis calculations, the largest equation is obtained on the fourth day of the study, the second point (Sound Level Meter 2), with a contribution of 32.42%. Obtained the calculation below, y = 63.36 + 0.002x1. This equation means that if there is no decrease in motorcycle density, the noise level in SLM2 is 63.36 dBA. If there is a motorcycle density also has a significant effect on noise. The second largest equation was obtained on the third day of research at the third point (Sound Level Meter 3) with a contribution of 36.21% based on the equation calculation below, y = 60.24 + 0.001x1. The meaning of the above equation is that if there is an increase in the density of the motorcycle, the noise in the SLM3 is 60.24 dBA. The Covid-19 pandemic that has hit the world, Indonesia is also getting its effects, especially the very large Bogor district. The rapid spread of Covid-19 has changed the pattern of life for the people of Bogor, especially students who initially go to school every morning, now go to school and study online.